REVITALISASI KERAJINAN BAMBU: TRANSFORMASI UMKM DI DESA MANISHARJO - Hariani Hariani; Hamka Hamka; Basri Basri (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Every year, Micro, Small, and Medium Enterprises (MSMEs) in Indonesia continue to grow and significantly contribute to community welfare. In Manisharjo Village, bamboo-based MSMEs create new job opportunities and reduce unemployment rates. However, with increasing competition at both national and international levels, bamboo MSMEs face major challenges in adapting and remaining competitive. University students have great potential to contribute to this transformation process through Community Service Programs, particularly in utilizing digital technology, product innovation, and marketing strategies. This study aims to explore the business tactics and innovations implemented by bamboo craft MSMEs in Manisharjo Village and to analyze the impact of the Community Service Program (KKN) on the development of these enterprises.